University administrative leadership trends towards the governance program of the Ministry of Higher Education and Scientific Research - كرم زامل الكناني, صبيح; يعقوب شحاذة, يوسف (Journal of College of Education, 2021)
E-governance exhorts everyone without exception because of the multiple benefits it offers in various fields, especially in his home, his beauty, his beauty, his beauty, his Pakistan, and the governance, which makes the expression of interaction bypassing the procedures of boring routine, contributing to the investment of time in all its parts.Educational administration and educational business plans. A descriptive and analytical approach was used, and the research community was identified with university leaderships in the universities of Iraq. The study sample reached (51) individuals.To achieve the results of the research, a trial version of (22) 4 gaps was made, as it was judged by its specialization, as its validity and reliability were confirmed.Statistical treatment: the practical application of the research tool, the application of surgical vacuum in a surgical area was used, and "SPSS" was used using the program of frequencies, averages, and standard deviations to obtain the results.The findings of the research:Administrative departments were acceptable. Its mean score was (28,642) degrees and a mean deviation of (3,462) degrees Celsius, which is smaller than the theoretical mean of the resolution (66) degrees.
Keywords: Directions, Administrative University Leaders, Ministry of Higher Education and Scientific Research.